Changes in Plasma Adiponectin Concentrations in Patients With Hemorrhagic Fever With Renal Syndrome: An Observational Prospective Study. Issue 6 (February 2016) - Du, Hong; Bai, Xuefan; Lian, Jianqi; Li, Jing; Zhang, Ying; Wang, Pingzhong; Jiang, Hong
Abstract : Abstract: The objective is to observe the changes in plasma adiponectin (APN) and its predictive capacity for disease severity and prognosis of hemorrhagic fever with renal syndrome (HFRS). One hundred and five patients who were treated at our center between October 2011 and December 2012 were randomly enrolled in this study. The patients were divided into a mild-type group, a moderate-type group, a severe-type group, and a critical-type group according to the HFRS criteria for clinical classification. Ninety-three plasma samples from the patients in the acute stage and 78 samples from the patients in the convalescent stage were obtained, and 28 samples from healthy subjects were obtained as controls. The concentrations of APN were detected using the enzyme-linked immunosorbent assay. The levels of white blood cells, platelets, hematocrit, albumin, blood urea nitrogen, serum creatinine, and uric acid in the samples were routinely tested. The levels of APN among the different types were compared; the correlation between APN and the laboratory parameters was analyzed. The predictive effectiveness for prognosis of APN and the laboratory parameters as mentioned above were evaluated using the receiver operating characteristic curve analysis. The levels of APN in the mild- and moderate-type patients in the acute stage were significantly higher than the severe-type and control ( P   <  0.05) and decreased with the severity of the disease, while there were no obvious difference among severe-, critical-type and control groups. The levels of APN in patients in the convalescent stage were higher than the control group ( P   <  0.05), and the APN levels of the critical-type group were higher compared with the mild-type groups ( P   <  0.05). Adiponectin was negatively correlated with white blood cells and hematocrit and positively correlated with platelets, albumin, and uric acid ( P   <  0.001). Adiponectin showed no statistical significance for predicting prognosis, with the area under the curve equal to 0.609 (95% CI: 0.237–0.745, P  = 0.215). Adiponectin can be considered as a novel biomarker for disease severity in patients with HFRS, while it seems to have no predictive capacity for prognosis of HFRS.